Physicochemical Quality and Health Risks Associated with Use of Water from Nyamwamba River, Kasese, Western Uganda - Masereka, Jockus; Byamugisha, Denis; Adaku, Christopher (Asian Journal of Applied Chemistry Research, 2022)
Aim: In Kasese district of Western Uganda, farmers cultivating near Nyamwamba River (NR) experience crop wilting whenever the river banks burst. Increased cases of cancer and ulcers in the district is anecdotally blamed on ingestion of contaminated water from water resources polluted by tailings from Kilembe copper mines. Sand miners attested that mining in NR caused body irritations and itching while drinking water from the same river results in abdominal complications in infants. The aim of this study was to assess the seasonal variations in the physicochemical parameters and heavy metals (HMs) content of water from NR, and the associated health risks. Place and Duration of Study: The experiments were done at the Department of Chemistry, Faculty of Science, Mbarara University of Science and Technology, Uganda from 2018 to 2019. Methodology: This study employed quantitative research design. Water was sampled from down, middle and upstream of NR and Mubuku River, Western Uganda during the dry and wet seasons. The samples were analyzed for physicochemical parameters (pH, conductivity, total dissolved solids, total suspended soils) and HMs: chromium (Cr), cadmium (Cd), zinc (Zn), iron (Fe), lead (Pb), arsenic (As) and copper (Cu) by atomic absorption spectrometry. The estimated daily intake (EDI), target harzard quotient (THQ) and cancer risks were calculated to explore if there are any carcinogenic and non-carcinogenic health risks that could arise from ingestion and dermal contact with water from NR. Results: Most physicochemical parameters of the water samples only met WHO guidelines for drinking water in the upstream. The mean concentration of Fe, Cu, Pb, Zn, Cr, Cd and As were 0.90-29.66 mg/L, 0.21-10.74 mg/L, 0.40-8.21 mg/L, 1.10-13.47 mg/L, 0.79-13.47 mg/L, 0.05-1.40 mg/L and 0.22-4.34 mg/L, respectively. Wet season recorded higher HMs concentrations when compared to the dry season, with all its samples exceeding the WHO guidelines for drinking water. There was an extremely high concentration of HMs in the upstream samples than expected. Health risk assessment indicated that the EDI through dermal contact ranged from 0.015 to 4.150 mg/kg/day while through ingestion of contaminated water, the values ranged from 0.008 × 10-6 to 38.266 × 10-6 mg/Lday. Some of the EDI doses were higher than corresponding reference doses for ingestion and contact with the HMs in water. THQ and total THQ exceeded 1 while cancer risk values were beyond the US EPA cancer risk borderline. Conclusion: This study revealed that there are serious non-carcinogenic and carcinogenic health risks that could arise from consumption and contact with water from NR. Future studies should examine the relationship between the occurrence of trace metals in food stuffs with cancer, ulcers and other associated diseases in the area.
Keywords: Cancer risk; Dermal adsorption; Estimated daily intake.; Hazard index; Target hazard quotient; Trace metals